2221. Active Substance Use Should Not Be a Contraindication for Hepatitis C Treatment in Hepatitis C and Human Immunodeficiency Virus Co-infected Patients. (26th November 2018) - Zeineddine, Nabil; Coppock, Dagan; Szep, Zsofia; Scott, Tiffany; Franks, Taneesa; Kesaris, Anna; Chou, Edgar; Lee, Dong Heun
Abstract: Background: Hepatitis C virus (HCV) infection disproportionately affects HIV-infected patients. HIV/HCV Co-infected patients are more likely to develop advanced liver disease/cirrhosis in comparison to mono-infected patients. HCV treatment with new oral direct-acting antiviral (DAA) therapy is effective in HIV/HCV co-infected patients with cure rate similar to mono-infected patients. Despite the effective treatments, only small portion of co-infected patients are treated for HCV infection. One of the known barriers to HCV treatment is active substance abuse. However, there is limited information about outcomes of HCV treatment with active substance abuse in HIV/HCV co-infected patients. Our primary aim was to evaluate Hepatitis C treatment outcomes in HIV/HCV co-infected patients with active substance abuse (ASA). Methods: We performed a retrospective cross-sectional study of HIV/HCV co-infected patients that were treated for HCV between 2014 and 2017 at Drexel University, Philadelphia, PA. We defined active substance abuse (ASA) by self-report of active drug use at the time of treatment evaluation. We described patient demographics and overall HCV sustained virologic response at 12 weeks after treatment. Results: One hundred thirty-eight HIV/HCV co-infected patients were treated. The majority ( N = 134, 97%) achieved sustained virologic response (SVR) after 12 weeks of treatment. Thirteen patients were active substance abusers, nine used cocaine, three used intravenous drug, and one used both. Twelve (92%) patients in the ASA group achieved SVR at 12 weeks in comparison to 122 (98%) in the non-ASA group ( P = 0.26). ASA group had a higher rate of psychiatry comorbidities in comparison to the none-ASA group (100% vs. 58%, P = 0.002). Conclusion: In our study, direct active antiviral HCV treatment was highly effective in HIV/HCV co-infected patients. Treatment outcomes were not different between active substance abuse group and none user group. Given co-infected patients have worsened prognosis with chronic HCV infection, active substance abuse should not be an absolute contraindication to HCV treatment. Disclosures: All authors: No reported disclosures.